Validity of the frame subtraction method in dynamic postural stability - Megumi Ota; Hiroshige Tateuchi; Takaya Hashiguchi; Karen Fujiwara; Ayano Sasaki; Kiseki Okumura; Noriaki Ichihashi (BMC, 2022)
Abstract Background The movement of targeted subjects can be calculated using the frame subtraction method. However, the validity of this evaluation method of dynamic postural stability has not been clarified yet. This study aimed to verify the validity of the evaluation method for jump landing using the frame subtraction score based on the ground reaction force (GRF). Methods Twenty subjects performed single-leg jump landing, and their dynamic postural stability index (DPSI), medial‒lateral stability index (MLSI), anterior‒posterior stability index, and vertical stability index (VSI) were calculated from the GRF. Simultaneously, motion images were captured using digital video cameras in the sagittal and frontal planes. After the motion images were analyzed using the frame subtraction method, the frame subtraction scores in the frontal, sagittal, and combined planes were calculated. To confirm its validity, the relationship between the frame subtraction scores and GRF parameters was investigated using Pearson's correlation analysis. Results The frame subtraction scores in the frontal and combined planes were significantly correlated with the DPSI, MLSI, and VSI (r = 0.46-0.75, P < 0.05). Conclusions Therefore, the frame subtraction method could be applied to the evaluation of dynamic postural stability. Markerless systems are deemed useful in clinical practice.